Livelihood of Former Jute Workers in and around Titagarh Jute Mill Area - Banerjee, Sraosri; Mondal, Pijus Kanti (International Journal of Scientific Research and Management (IJSRM), 2017)
There is a significant role of jute industry in Indian economy with one of its most important centres in WestBengal, specifically in Hooghly basin. It is given the title of the ‘Golden Fibre’ internationally with its highversatility and cheap price. But unfortunately its market is deterioration with decrease in productivity. Suchdeterioration has resulted in closing down of various mills stretching its effects on the workers engaged inthem. This study deals with the effect on livelihood of former labours of the industry of Titagarh, a majorzone concentrating jute mills in north 24 parganas in the left bank of river Hooghly.. The main objectives ofthe study are to bring out the present scenario of livelihood of former jute workers in and around TitagarhJute Mill area concentrating in Ward 1, 2 and 3 and illustrate the physical and socio economic attributes thatencompasses them. The research is done based on quantitative and qualitative methods based on structuredquestionnaires on sample size summing up to 150 based on direct interviews with 50 from each ward, andsecondary data from various sources. It is found out that the physical setting have provided favourableconditions for settling up of the industry and attracting labours to settle down around it. Unfortunately afterclosing down of the mills, the conditions of the former workers have deteriorated with dense settlement andlower standard of living which need attention for development. Unfortunately, the deteriorated conditionsare intermingled with social unrest and disruptions